Percepção dos trabalhadores sobre as mudanças na organização do trabalho decorrentes da adoção da produção enxuta - Pacheco, Orjana de Oliveira (2012)
The adoption and the organization of a new a production system reproduces changes not only to the work organization, but for people involved in this environment. From the second half of the twentieth century, in answer to the depletion of mass production system, lean production system comes at Toyota, the company localized in Japan. This production model has the main characteristics like wastes reduction, quality continuous improvement, work processes flexibility, team building, besides others aspects that provided the answer to the market request. Several scholars defect lean production as the production model capable that provides a better work environment for the workers, with better organization and a professional qualification increase. Other theorists, however, consider lean production as a new model of work intensification, with practices that, although they advocate the qualification increase, lean production increases the work rhythm and the work responsibility. This dissertation aims to confront this theorical duality existing among the lean production scholars in the literature with a case study on the workers perception about the adoption of the lean production tools in a metalworking company. As a result of this case study, the workers indicate positive and negative effects. The positive effects show the work improvement with the chance to learn new functions (multifunctionality), the introduction of new technologies, the possibility to learn knowledge of new production techniques, a work organization rearrangement, a better sector organization (5S Program), the possibility of participating in kaizen (factory), and the change in the physical work environment (the transformation of the cell layout). The negative effects mentioned were these: the increased of the workload, the work rhythm and work pressure, they generated by the new organization, the withdrawal of some intervals of work, lack of wage increases. Some suggestions are left for companies that will adopt the tools of lean production, that will contribute to the success of this adoption: to introduce new concepts, you need to add the workers since the beginning of the process, so they can participate better in the process; you need to elucidate with clarity and transparency the objectives of each change, and what is expected of each employee, because many of them can consider the lean production as something negative because they don´t know the lean production goals and consequences.